2018
DOI: 10.3171/2017.12.spine171079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of racial disparities on patient-reported satisfaction and short- and long-term perception of health status after elective lumbar spine surgery

Abstract: OBJECTIVEIn spine surgery, racial disparities have been shown to impact various aspects of surgical care. Previous studies have associated racial disparities with inferior surgical outcomes, including increased complication and 30-day readmission rates after spine surgery. Recently, patient-reported outcomes (PROs) and satisfaction measures have been proxies for overall quality of care and hospital reimbursements. However, the influence that racial disparities have on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
5
33
1
Order By: Relevance
“…Elsamadicy et al, in their study of 345 patients who had undergone elective lumbar surgery, demonstrated that African American patients were more likely to report lower satisfaction with their surgery at 3 months and at 1 year. 15 In their meta-analysis of 128,635 patients who had undergone spine surgery, Schoenfeld et al showed that non-white patients had a higher risk of an unfavorable outcome than their white counterparts. 39 In a corollary study of the Spine Patient Outcomes Research Trial (SPORT), Schoenfeld et al documented better PROs in white patients than in African American patients regardless of the treatment arm (surgical intervention and nonoperative management).…”
Section: Discussionmentioning
confidence: 99%
“…Elsamadicy et al, in their study of 345 patients who had undergone elective lumbar surgery, demonstrated that African American patients were more likely to report lower satisfaction with their surgery at 3 months and at 1 year. 15 In their meta-analysis of 128,635 patients who had undergone spine surgery, Schoenfeld et al showed that non-white patients had a higher risk of an unfavorable outcome than their white counterparts. 39 In a corollary study of the Spine Patient Outcomes Research Trial (SPORT), Schoenfeld et al documented better PROs in white patients than in African American patients regardless of the treatment arm (surgical intervention and nonoperative management).…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed between the YML and YWH subgroups were the most profound among the subgroups, especially with patient satisfaction, which exhibited the widest variation in success probability. The influence of various SDoH such as insurance and race on patient satisfaction has been previously documented in the surgical literature [17,50]. The disparities seen in pain and disability have not previously been observed and begin to justify the need for more robust methods of quantifying the relationships between various SDoH [4,51].…”
Section: Plos Onementioning
confidence: 97%
“…Five pre-operative SDoH variables were selected based on the Commission on Social Determinants of Health Final Report published by World Health Organization [22]. The variables included race/ethnicity, educational attainment, employment status, insurance payer, and gender, which were dichotomized based on previous research findings [4,17,[23][24][25][26] to improve interpretability of findings.…”
Section: Study Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other racial and ethnic groups are often studied together as a combined cohort, rarely reporting on the burden encountered specifically as it relates to these racial populations. 5,8 -14 Little to no data is currently available regarding Native American (NA) recipients of spinal surgery or among the field of orthopedic surgical research at large. 15 This is of special concern considering the increased incidences of multiple health conditions including obesity, diabetes, physical disability, and substance abuse observed in NA communities often within the context of staggeringly low access to health care.…”
Section: Introductionmentioning
confidence: 99%